Determinants of liking : a call for multilevel assessment of wine preferences – a commentary on Werner and colleagues 2021 - Setoh, Peipei (2021)
In their interesting article, Werner and colleagues (Werner et al., 2021) found that deceptive up-pricing of cheap wine increased participants’ liking of the wine. Prior to their study, no other field study has examined consumers’ ratings of wines where only price information was experimentally manipulated (see however Mastrobuoni, Peracchi, & Tetenov, 2014 for a field experiment on effects of landscape images and randomly assigned price on tasters’ ratings of prosecco, merlot and tocai). Werner and colleagues’ study fills this gap in the literature by performing a field experiment which measured participants’ liking of three red wines at different price points twice - once without price information, and another time under the influence of price. Werner and colleagues found that the lowest priced wine was liked more when it was deceptively up-priced, in line with other research on the effect of price where demand or liking increased as price increased (Mastrobuoni et al., 2014; Plassmann, O’doherty, Shiv, & Rangel, 2008). Werner and colleagues were interested in how the subjective experience of wine will be influenced by price information of the wine. Subjective experience of wine was defined as “an umbrella term for pleasantness and taste intensity”, and hence pleasantness (measured by participants’ liking of the wine) and intensity were the two dependent variables of interest.